2019
DOI: 10.1002/pc.25129
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide‐wrapped polyaniline nanorods for supercapacitor applications

Abstract: This study depicts the chemical synthesis and supercapacitive behavior of nanocomposites of Polyaniline nanorods wrap with graphene oxide (PANI/GO). Synthesis of PANI/GO nanocomposites was carried out by in situ oxidative solution polymerization of aniline in the presence of Nitric acid, acting as a proton donor. The nanocomposites were characterized by field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), Fourier transform infrared spectroscopy, X‐ray diffraction, Raman … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 57 publications
(110 reference statements)
0
18
0
Order By: Relevance
“…Bharadiya et al had studied the electrochemical properties of GO‐wrapped PAni composites (Figure ). They observed that the wrapping of monolayer (1) and multilayer (2 to 10) of GO sheets on PAni nanorods led to an increase in the d ‐spacing of the GO sheets from 12.76 Å for PAni/GO1 to 13.46 Å for PAni/GO10.…”
Section: Application Of Polyaniline In the Field Of Supercapacitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bharadiya et al had studied the electrochemical properties of GO‐wrapped PAni composites (Figure ). They observed that the wrapping of monolayer (1) and multilayer (2 to 10) of GO sheets on PAni nanorods led to an increase in the d ‐spacing of the GO sheets from 12.76 Å for PAni/GO1 to 13.46 Å for PAni/GO10.…”
Section: Application Of Polyaniline In the Field Of Supercapacitorsmentioning
confidence: 99%
“…A schematic diagram depicting the preparation of graphene oxide (GO)–wrapped polyaniline (PAni) nanorods . Reproduced with permission from Wiley…”
Section: Application Of Polyaniline In the Field Of Supercapacitorsmentioning
confidence: 99%
“…Attraction to supercapacitors (SCs) has been developed as a reliable energy storage device due to fast charge/discharge features, outstanding cycle stability, and grand‐power density. And also, many investigations have been done to overcome low‐energy density drawbacks through the designing and application of efficient electrode materials where fabricated in SCs to develop more durable and appropriate electrochemical performances . Physicochemical properties of the electrode such as their size, shape, porosity, and surface charge influenced the performance of electrode and are important for their applications.…”
Section: Introductionmentioning
confidence: 99%
“…And also, many investigations have been done to overcome low-energy density drawbacks through the designing and application of efficient electrode materials where fabricated in SCs to develop more durable and appropriate electrochemical performances. [1][2][3][4][5][6][7][8][9][10][11][12][13] Physicochemical properties of the electrode such as their size, shape, porosity, and surface charge influenced the performance of electrode and are important for their applications. To develop the performance of SC devices, many researches have been accomplished to employ conductive polymers, [14][15][16][17] metal and metal oxides, [18][19][20][21][22][23][24][25][26] and carbonaceous materials.…”
Section: Introductionmentioning
confidence: 99%
“…on the surface of GO sheets endow them with good dispersity in polymer composites. [15][16][17][18][19][20] Also, to further facilitate the chemical cross-linking with the matrix, some active organics (e.g., silane coupling agents) are commonly used for the functionalization of GO. [21][22][23] Recently, the deposition of GO on the fiber surface for creating a hierarchical structure has attracted great interest.…”
mentioning
confidence: 99%